Estimation of Spatiotemporal Changes of Land Cover in Llapi River Catchment (Northeastern Part of Kosova) - Valbon Bytyqi; Besarta Ibrahimi; Tropikë Agaj (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: In recent decades, Kosovo in general and the Llapi River catchment in particular have experienced landscape transformation, which resulted in Land Use and Land Cover (LULC) changes, mainly in the flat terrains where most of country’s population is concentrated. Other landscapes have experienced changes too, but on a smaller scale. The aim of the present study was to identify landscape transformation and driving forces behind it.